Pemahaman Konsep Pasar Uang Dalam Perspektif Ekonomi Islam: Konstruksi Pasar Uang Islami - Tristiyana Sari, Dhea Novita; Saifulloh, Achmad Ramadhani; Islam, Farhan Muhammad; Syihabuddin, Atok; Roziqin, Muhammad Choirur (Universitas Muhammadiyah Sumatera Utara, 2024)
This study investigates the concept of the money market from the Islamic economic point of view and the construction of the islamic money market. The money market is a short-term fund trading system, in which an entity in need of funding meets with a party that has an excess of funds. In the context of Islamic economics, the Islamic money market operates on the basis of Sharia principles. This study aims to look at the money market from an Islamic economic perspective. The method used in this research is the theoretical expression by collecting and analyzing relevant literature. The results of this study show that the Islamic money market plays an important role in Islamic finance, providing the monetary foundation for Islamic financial practices and protecting sharia banks from liquidity and credit risks. The Islamic money market also plays a role in supporting import and export activities as well as labour capital needs. However, there are still challenges and difficulties in implementing the Islamic money market due to the lack of provisions of Islamic law governing its implementation. The conclusion of this study is that the money market in the Islamic perspective should be avoided from the elements of speculation, interest, maisir, and gharar. Furthermore, the Islamic money market has the same potential as the conventional money market, but with operational compliance with the principles of Shariah. This research provides a better understanding of the money market in the context of Islamic economics and provides a basis for further development in the Islamic financial industry.